2014
DOI: 10.4193/rhin13.222
|View full text |Cite
|
Sign up to set email alerts
|

The determining factors of peak nasal inspiratory flow and perception of nasal airflow in asthmatics

Abstract: Background: The effect of pulmonary pathology on peak nasal inspiratory flow (PNIF) remains largely unknown. We investigated an association between a diagnosis of asthma and of lung function on PNIF when adjusted for possible confounders. Further, we investigated the perception of nasal obstruction in asthmatics compared to healthy controls when adjusted for PNIF.Methodology: Eighty-seven asthmatics and 92 non-asthmatic controls underwent PNIF (categorized into groups of high, medium and low), acoustic rhinome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…PNIF has been shown to be highly reproducible (15) and well suited to identify patients with clinically relevant nasal stenosis (16,17) . It is positively correlated with pulmonary ventilatory capacity measured by peak expiratory flow (PEF) (18) , male sex, height and inversely with age (12) and asthma status (19) . PNIF correlates and compares to the gold standard of nasal airflow measurement, rhinomanometry (20)(21)(22) , and acoustic rhinometry (23) .…”
Section: Patient Demographicsmentioning
confidence: 99%
“…PNIF has been shown to be highly reproducible (15) and well suited to identify patients with clinically relevant nasal stenosis (16,17) . It is positively correlated with pulmonary ventilatory capacity measured by peak expiratory flow (PEF) (18) , male sex, height and inversely with age (12) and asthma status (19) . PNIF correlates and compares to the gold standard of nasal airflow measurement, rhinomanometry (20)(21)(22) , and acoustic rhinometry (23) .…”
Section: Patient Demographicsmentioning
confidence: 99%
“…As in asthma, it has been clearly shown that symptoms and objective measurements do not always correlate well , and the assessment of a patient suffering of nasal obstruction should be based upon both subjective and objective measures. On the one hand, patients with objective nasal obstruction do not always have symptoms , but on the other hand, the correlation between symptoms and objective measurements is far from obvious . It has been suggested that objective measurements do not correlate very well with subjective measurements of nasal obstruction, because the nasal valve region primarily determines nasal resistances, while the sensation of nasal obstruction may be related to congestion in other areas of the upper airway, such as the ethmoid region Nathan et al.…”
Section: Correlation Between Symptoms and Objective Testsmentioning
confidence: 99%
“…This needs to be analysed in future studies with larger samples, but it could be influenced by the fact that CARATkids questionnaire considers nasal symptoms self-reported by the children regarding the last two weeks and not necessarily current symptoms at the time of PNIF measurement. Moreover, in a previous study in adults, patients with asthma significantly rated their nasal obstruction by visual analogue scale more seriously than non-asthmatic controls with comparable PNIF values (29) .…”
Section: Association Between Pnif Lung Function Variables and Fenomentioning
confidence: 66%
“…Apparently, the sensation of nasal obstruction in asthmatics may be different from controls despite being in the same PNIF group (29) . On the opposite direction, children on long-term treatment for chronic rhinitis may underreport the amount of nasal congestion (44) , and it has been reported that children may be more accepting of mouth-breathing than adolescents (43) .…”
Section: Association Between Pnif Lung Function Variables and Fenomentioning
confidence: 91%
See 1 more Smart Citation